Pendidikan Rasa Al-Ghazali: “Gak Cuma Pintar, Hati Juga Kena!” - Fhina Ardini; Niesa Amalia; Herlini Puspika Sari (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This research responds to the contemporary educational crisis dominated by cognitive intelligence ('aql) resulting in the phenomenon of "smart but dry," by proposing Al-Ghazali's concept of "Education of Feelings" as a solution. The aim is to explore the concept, methods, and relevance of "Education of Feelings" to balance the intellectual and spiritual dimensions. This descriptive qualitative research uses library research on Al-Ghazali's works. The results show that "Education of Feelings" is a transformative effort that emphasizes the integration of knowledge through reason and intuition (dzawq), with the qalb (spiritual heart) as the center of knowledge reception. Its pedagogical core is the process of purifying the soul (Tazkiyatun Nafs) so that knowledge is beneficial (Ilm Nafi') and culminates in ma'rifah (true knowledge) and moral perfection (al-insan al-kamil). Practically, relevant methods include teacher role models (uswah hasanah) and learning based on deep reflection. This concept is relevant in the digital age because it serves as a spiritual bulwark, offering peace of mind (sakinah) and an ethical filter (dzawq) to counter individualism and information disruption. Consequently, Islamic Religious Education (PAI) education is advised to reconstruct its curriculum and evaluation to include a portfolio assessment of morals, in order to shape a cognitively intelligent and spiritually mature generation.